Streptomyces sp. MUM 195J: A Promising Probiotic for Controlling Vibrio parahaemolyticus Infection in Aquaculture - Joanna Xuan Hui Goh; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Giva Kuppusamy; Janaranjani M; Kooi-Yeong Khaw; Wei Hsum Yap; Kok-Gan Chan; Vengadesh Letchumanan; Learn-Han Lee; Bey-Hing Goh (Progress in Microbes and Molecular Biology)
Aquaculture is gaining prominence in meeting the increasing global food demand. However, persistent episodes of pathogenic infections have greatly affected production and incurred substantial financial losses to the industry. Regrettably, there is a lack of effective contemporary therapeutic measures to control infectious diseases in aquaculture. The repercussions of antimicrobial resistance have underscored the drawbacks of the contemporary practice of relying solely on antibiotics in disease control. The aquaculture industry needs a safer, environmentally viable, and economically efficient means for disease management. In this regard, this study aims to investigate the effectiveness of mangrove-derived Streptomyces sp. probiotics in controlling Vibrio parahaemolyticus infections. In vitro screenings were undertaken to evaluate the inhibitory activity of five Streptomyces sp. isolates. Subsequently, a series of in vivo trials was conducted, with the Malaysian giant freshwater prawn, Macrobrachium rosenbergii larvae as the animal model. Following that, molecular analyses were employed to examine the changes in gene expression. In essence, Streptomyces sp. MUM 195J emerges as a promising probiotic strain that demonstrates a strong inhibitory effect against V. parahaemolyticus. Its application as a feed additive elevates the survival rate of M. rosenbergii threefold, thus demonstrating efficacy at par with florfenicol antibiotic when challenged with the V. parahaemolyticus pathogen. Besides, Streptomyces sp. MUM 195J elevated the growth rate of M. rosenbergii by 17%. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis revealed that probiotic supplementation elevated the immune function of the animal. Additionally, Streptomyces sp. MUM 195J demonstrates the potential to ameliorate the quality of the rearing water.